Agricultural economic growth, renewable energy supply and CO2 emissions nexus - Tagwi Aluwani (Economies, 2023)
International trade has created more economic growth opportunities in the agriculture sector. The agricultural sector remains key to the South African economy, with a vibrant international market becoming available as the country's agriculture exports grow. However, the impacts of human-caused global warming have intensified as a result of increased greenhouse gas emissions, notably carbon dioxide (CO2), which negatively affects agricultural productivity and the economy. Considering the future energy resource demands for agricultural productivity due to the expected population growth and the emphasis on environmental remedial actions, the following question presents itself: what impact will a clean energy supply have on the agricultural economy and the environment, notwithstanding that agriculture, as a sector, also has a huge potential to contribute to renewable energy production? This study examines the effect of the nexus of South Africa's renewable energy supply, CO2 emissions and trade openness on agricultural economic growth from 1990 to 2021. The nexus provides crucial insights into policies targeted at promoting renewable energy in the agricultural sector by isolating key areas of priority. An autoregressive distributed lag (ARDL) bounds test, fully modified ordinary least square (FMOLS) test, a dynamic ordinary least square (DOLS) test and a canonical cointegrating regression (CCR) econometric analysis were used to estimate the nexus. The results showed that growth in the agricultural sector leads to deterioration in the environment, while international trade benefits the sector. The scale of renewable energy supply slowed down the agricultural economy. The study makes a new contribution in providing empirical evidence for the links between renewable energy supply and agricultural GDP, which can drive policy on renewable energy use in the agricultural sector in South Africa. The paper recommends intentional renewable energy production research and development (R&D) finance focusing on renewable energy human development planning and investments in vocational programmes in higher learning institutes, agricultural renewable energy policy and the creation of green incentive schemes for feedstock producers, especially in rural areas in the agricultural sector.
Keywords: 330; agricultural economic growth; ARDL; economic growth; error correction model; renewable energy; South Africa